Rancang Bangun Instalasi Aquaponik Sederhana Sistem Deep Flow Technique di Lahan Pekarangan - Umami, Arif; Faris Mu'taz, Ade; Taufik Amin, Ja'far; Azhar Riza, Aulia (Universitas Pembangunan Nasional Veteran Yogayakarta, 2023)
One aspect of success in aquaponic cultivation is a suitable installation to support the growth of plants and fish. Good nutritional water quality is needed in aquaponic cultivation for the survival of fish and plants. Aquaponic systems could use several systems to deliver nutrients or water to plants. One system that could be used is the DFT (Deep Flow Technique) system. The DFT system for simple aquaponics requires a design and its implementation in the yard. So, in this article, the design and implementation of a DFT system for simple aquaponics in the yard were discussed. The design results have been successfully realized. DFT aquaponic trials on rice-tilapia plants resulted in normal growth of plants and fish even though harvest data were not recorded. Subsequent trials on DFT aquaponic vegetable- catfish produced an average wet weight per plant for the Grand Rapids lettuce was 15,526 gr, Red Rapids was 60,916 gr, Green romaine was 48,630 gr, and star lettuce was 33,106gr. Meanwhile, the average yield obtained from the Tosakan variety was 31,466 gr per plant, Shinta was 38,576 gr, New White Light was 10,116 gr, and Chinese Kale New Veggin was 18,678 gr/plant. Catfish harvested were 100 - 200g per fish with SR value> 80%.